Optimizing Lightning Arrester Selection for 275kV EHV Substations: A Comparison of Overvoltage Analysis with Software and Manual Calculations - Bagus Irawan Saputra; Siregar, Marsul; Panjaitan, Lanny W (JURNAL NASIONAL TEKNIK ELEKTRO, 2025)
A substation is one of the essential aspects of an electrically interconnected system, especially in a grid utility. Power generation, transmission, and distribution systems always need a continuous power supply to the customer. In high voltage and extra high voltage substation, operation schemes during abnormal and normal conditions may cause transient overvoltage in the system, one of which is temporary overvoltage. Temporary overvoltage analysis is needed to validate the rated system voltage within the limit of the substation equipment’s insulation level, including the rating of the lightning arrester. This research will select a lightning arrester with the standard approach IEC 60099-5 and software simulation on a computer. Conducted temporary overvoltage analysis using software simulation, which resulted in a value of 2.02 pu higher than the operating voltage. This slightly differs from the IEC 60099-5 standard, which recommends a value of 1.6 pu of operating voltage. Software simulation is beneficial as it models the system according to specific network parameters, leading to an optimal selection when compared to standards with different approaches to results based on varying network parameters. Temporary overvoltage analysis could help determine the correct rating of the lightning arrester and further mitigation, such as line compensation, switching technique, and load management, ultimately leading to reliability in substation equipment and interconnection system networks.